Association of juvenile traits in full-sib and half-sib progenies of Hevea brasiliensis - Gireesh T; Pravitha M (National Conference on Tree Improvement Research in India: Current Trends and Future Prospects, 2-3 February 2017, Institute of Wood Science and Technology, Bengaluru, India. Abstracts. p.95.)
Hevea brasiliensis, the Para rubber tree, produces the lion share of world natural rubber. Lack of reliable early selection parameters for important agronomic traits is one of the handicaps in breeding, especially for earliness and potential timber-latex clones. Five hybrid clones (RRII 400 series) of H. brasiliensis with high rubber yield and timber output were subjected to further recombination breeding. Half-sib and full-sib progeny population were developed for primary selection. Phenotypic diversity among 465 progenies was assessed using morphological descriptors and five measurable traits were used for phenotypic correlations. Results indicate that the half-sib all full-sib progenies could be categorised into three distinct groups with similarly coefficient of 40 to 50 per cent based on Dice index. Similarity among the open pollinated progenies was about 40 per cent. Group I (15 progenies), group II (92 progenies) and group III forms the largest group with 124 half-sib progenies. Full sibs also grouped into three: group I with five, group II with 169 and group III with 60 progenies. Most of the vigorous progenies among the half-sibs and full sibs confined to group I indicates directional selection. The results also indicate that existence of moderate level of variation within and between families. Significant positive correlation (p<0.05) found among the progenies between traits like plant height and girth; plant height and number of whorls. Instead of measuring girth of the plant, which needs more time and labour, measuring height is rather easy and even visually possible in large observation nurseries with thousands of progenies. It may be possible that selecting vigorous genotypes based on height of the progenies as an early indicator could maximize the selection efficiency when breeding for timber-latex clones or early maturing varieties.
Keywords: Full-sib; Girth; Half-sib; Height; Hevea brasiliensis; Variation